MORAL-ETHICAL ASPECTS OF THE DIGITAL ECONOMY - A. A. Sychev; E. V. Zaytseva; P. S. Tolkachev (Вестник университета)
At the present stage, the digital (information) economy is playing an increasingly important role in the world economy and national economies. Using rapid exchange of information benefits allows economic agents at all levels (from ordinary consumers to large corporations and state bodies, regulating economic relations) to make more accurate decisions in various economic issues. It is obvious, that the creation of the Russian information system will be able to increase the efficiency of our national economy (including the objectives of its state regulation) and at the same time raise the level of the country’s security. However, the effective use of the digital economy does not only depend on the level of development of the technical base of the information system. Only the moral state of society can send the information received for the benefit of all its members.